Case report: Intra-abdominal inflammatory myofibroblastic tumor with mucinous features: a case of rapid recurrence and dissemination post-surgery - Li, Xingchen; Li, Jie; Liang, Chunxiao; Zou, Qing (Frontiers in Oncology, 2025)
Inflammatory myofibroblastic tumors (IMTs) are rare mesenchymal neoplasms with intermediate biological potential and are characterized by spindle-shaped myofibroblastic cells and significant inflammatory infiltrates. This case report describes a 24-year-old male with diabetes who was admitted to the hospital for over three days of vomiting and abdominal pain and was initially diagnosed with diabetic ketoacidosis. Upon admission, an abdominal CT scan revealed a large cystic-solid mass in the abdominal cavity and multiple nodules in the mesentery, omentum, and peritoneum, suggesting a preliminary diagnosis of an intra-abdominal mesenchymal tumor with peritoneal metastasis. The patient underwent tumor resection, and postoperative pathology confirmed it to be an IMT rich in mucin, with a Ki-67 proliferation index of 50%. Despite the initial symptom improvement after surgery, the patient experienced rapid recurrence with more extensive abdominal lesions. The patient refused further treatment, and died shortly thereafter. The case underscores the aggressive nature of inflammatory myofibroblastic tumors (IMTs) characterized by significant mucinous features, which are prone to recurrence and may suggest a poor prognosis. Radiological examinations and preoperative fine-needle aspiration biopsy may play a crucial role in managing such cases. Furthermore, alternative non-surgical treatment options or adjunct postoperative treatments could have a positive impact on the prognosis of this patient group. Further research is vital for enhancing our understanding of this rare tumor type and optimizing treatment strategies.